2020
DOI: 10.3390/rs12152361
|View full text |Cite
|
Sign up to set email alerts
|

First Measurement of Soil Freeze/Thaw Cycles in the Tibetan Plateau Using CYGNSS GNSS-R Data

Abstract: The process of soil freezing and thawing refers to the alternating phase change of liquid water and solid water in the soil, accompanied by a large amount of latent heat exchange. It plays a vital role in the land water process and is an important indicator of climate change. The Tibetan Plateau in China is known as the “roof of the world”, and it is one of the most prominent physical characteristics is the freezing and thawing process of the soil. For the first time, this paper utilizes the spaceborne GNSS-R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…They were obtained from microwave radiometer products, i.e., the SMAP L3 daily products, version 5, projected onto the Equal-Area Scalable Earth (EASE) Grid, and the SMOS Level 3 product. It must be pointed out that VOD is not a vegetation parameter that can be measured on the ground, but it is rather an electromagnetic parameter that is correlated with the vegetation biomass and height [30]. MODIS/Terra Normalized Difference Vegetation Indices (NDVIs) generated every 16 days were also collected.…”
Section: Dataset Description and Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…They were obtained from microwave radiometer products, i.e., the SMAP L3 daily products, version 5, projected onto the Equal-Area Scalable Earth (EASE) Grid, and the SMOS Level 3 product. It must be pointed out that VOD is not a vegetation parameter that can be measured on the ground, but it is rather an electromagnetic parameter that is correlated with the vegetation biomass and height [30]. MODIS/Terra Normalized Difference Vegetation Indices (NDVIs) generated every 16 days were also collected.…”
Section: Dataset Description and Calibrationmentioning
confidence: 99%
“…Some data collected by the airborne GLORI sensor [12], [17] in France and the CORTO sensor [18] in Spain were also analyzed and compared to the spaceborne case to understand at what extent the platform height can affect both sensitivity and retrieval capability. Another promising application of GNSS-R over land was also investigated, that is the monitoring of freezethaw soil conditions in subarctic areas [28], which has attracted scientific interest from different groups [29], [30], [31], [32].…”
Section: Introduction and State-of-art On Gnss Reflectometrymentioning
confidence: 99%
“…More recently, some pioneering studies have shown a promising sensitivity to F/T surface state transitions over high latitude regions, including SMAP GNSS-R mode [34], [39] and TechDemoSat-1 [40]; and also CYGNSS [41]. CYGNSS [30] was originally proposed for ocean surface winds speed estimation over tropical cyclones using reflected L1 Global Positioning System (GPS) signals at left-handed circular polarization (LHCP).…”
Section: Introductionmentioning
confidence: 99%
“…Although spaceborne GNSS-R has been extensively used to estimate the wind speed on oceans [11,12], its land application is challenging. At present, most of the applications of spaceborne GNSS-R on the land surface used DDM (delay-Doppler map) measurements from the CYGNSS platform and focused on the hydrology variables such as soil moisture [13,14], lake water level [15], wetland extent [16], soil freezingthawing [17], and flooding area [18][19][20]. GNSS-R has strong responses to the inland water caused by coherent forward scattering, leading to studies on its ability for permanent inland water detection.…”
Section: Introductionmentioning
confidence: 99%